The State of the Hemostasis System in Pregnant Women with Respiratory Viral Infection (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Seasonal viral infections in the process of human civilization manifested themselves through various viral infections. In the XXI century in the history of human, COVID-19 became a global problem and was the cause of a pandemic around the world, and today this virus has become a seasonally aggravated viral infection. Bu virus ҳam ҳomiladorlik davrida aellar sogligida zhiddi muammolarni keltirib chikarishi mumkin. This virus can also cause serious health problems during pregnancy. The aim of the study: assessment of the state of the hemostasis system in pregnant women with seasonal viral infections. The research materials were selected 49 pregnant women hospitalized in maternity complexes of the Samarkand region for seasonal viral infections. In the results of the study, we mainly paid attention to the general condition of women depending on the trimester of pregnancy, the reasons for hospitalization, comorbid conditions, changеs in general tests, coagulogram, in the blood coagulation system, as well as the outcomes of pregnancy and childbirth. Conclusion. Since the possibility of complete elimination of seasonal viral infections has not been discovered, much remains to be learned about the impact of viral infections on the course of pregnancy, given the incomplete study of the development of possible complications, it is necessary to study more deeply many aspects of the influence of seasonal viral infections on pregnancy, as well as on perinatal and neonatal outcomes.